2015
DOI: 10.1152/ajpregu.00153.2014
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-binding protein, spermatid-specific 1 is expressed in human salivary glands and contains an anti-inflammatory motif

Abstract: Salivary glands are involved in the production and exocrine and endocrine secretion of biologically active proteins, polypeptides, and hormones involved in growth and differentiation, homeostasis, and digestion. We have previously studied the prohormone submandibular rat 1 (SMR1), product of the Vcsa1 gene, which is highly expressed in the testes and salivary glands of rats, and can be cleaved to produce polypeptides with analgesic, erectile function, and anti-inflammatory activities. Humans lack the Vcsa1 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 34 publications
6
43
4
1
Order By: Relevance
“…In agreement with this observation, we have shown that N-or O-glycanase treatment does not alter CABS1 M r in SDS-PAGE, suggesting that glycosylation events do not explain the discrepancies in M r of the protein. 12 Other posttranslational modifications like phosphorylation have been observed for CABS1 in vivo. 36 However, a single phosphorylation event only contributes 80 Da in M r .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In agreement with this observation, we have shown that N-or O-glycanase treatment does not alter CABS1 M r in SDS-PAGE, suggesting that glycosylation events do not explain the discrepancies in M r of the protein. 12 Other posttranslational modifications like phosphorylation have been observed for CABS1 in vivo. 36 However, a single phosphorylation event only contributes 80 Da in M r .…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, a model of intestinal anaphylaxis showed that "TxI" was not necessary to elicit anti-inflammatory activity. 12 We observed that "FELL" elicited this activity and postulated that this tetrapeptide contains the core anti-inflammatory component. 12 Moreover, a Shannon entropy analysis indicates that the anti-inflammatory sequence displays noticeably lower level of entropy in primates ( Figure S1).…”
Section: Amino Acid Sequence Conservation Of Cabs1mentioning
confidence: 92%
See 3 more Smart Citations